Selective synthesis of α- and β-glycosides of N-acetyl galactosamine using rare earth metal triflates - Wang, Jiajia; Zhang, Wei; Cao, Wei; Liu, Kang; Su, Shihao; Ma, Jing; Li, Xia (Frontiers in Chemistry, 2022)
Structures containing galactose and GalNAc residues are specifically recognized by asialoglycoprotein receptors, allowing them to selectively internalize by hepatocytes for drug-targeting delivery. However, methods for direct synthesis of GalNAc glycosides are still challenging due to the poor participating group of 2-acetamido. Here, we develop a facile strategy to synthesize various GalNAc glycosides by employing a series of rare earth metal triflates, and the results demonstrate that both α-glycosides and β-glycosides of GalNAc can be obtained by conducting with Hf(OTf)4 and Sc(OTf)3, respectively. These applicable results indicate that any interested GalNAc-containing substrates could be prepared by this simple strategy.